Youth, arts, and education : reassembling subjectivity through affect - Hickey-Moody, Anna, 1977- (Routledge advances in sociology ;, 2013)
"How are the arts important in young people's lives? Youth, Arts and Education offers a groundbreaking theory of arts education. Anna Hickey-Moody explores how the arts are ways of belonging, resisting, being governed and being heard. Through examples from the United Kingdom and Australia, Anna Hickey-Moody shows the cultural significance of the kinds of learning that occur in and through arts. Drawing on the thought of Gilles Deleuze, she develops the theory of affective pedagogy, which explains the process of learning that happens through aesthetics. Bridging divides between critical pedagogical theory, youth studies and arts education scholarship, this book: - Explains the cultural significance of the kinds of learning that occur in and through arts - Advances a theory of aesthetic citizenship created by youth arts - Demonstrates ways in which arts practices are forms popular and public pedagogy - Critiques popular ideas that art can be used to fix problems in the lives of youth at risk Youth, Arts and Education is the first post-critical theory of arts education. It will be of interest to students and scholars across the social sciences and humanities, in particular in the sociology of education, arts education, youth studies, sociology of the arts and cultural studies"--